2013
DOI: 10.4028/www.scientific.net/amm.315.675
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Molten Sn-Zn-Bi Solder on Cu Substrate Ervina Efzan

Abstract: This work presents the studies of wettability Sn-6Zn-4Bi lead-free solder alloy in electronic applications. A reference solder Sn-3.1Ag-0.9 Cu lead-free solder alloy is used to compare the properties of both solders. Differential Scanning Calorimeter (DSC) profile, wettability and the microstructure of the solder were investigated. The melting temperature of Sn-Zn-Bi (Tm=194.97°C) is lower than Sn-Ag-Cu (Tm=220.40°C). Further, the wettability between molten solder and copper substrate was measured at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…This correlated with the formation of eutectic Sn-3.5Ag-0.5Cu (SAC) solder by the addition of Cu in the SA solder (Zhang et al, 2012a;Kotadia et al, 2012). Meanwhile, the overall contact angle for Sn-3.1Ag-0.9Cu (SAC) was within 20 to 30°, and the SAC solder showed better wettability at a reflow temperature of 250°C by producing a larger spreading area and lower contact angle (Ervina and Tan, 2013). Although the wettability of the SAC was Ͻ 50°, and this angle was sufficient to produce better joints (Noor et al, 2010), little research has been done based on the wettability of the SAC solder system.…”
Section: Wettability Properties Of Sacmentioning
confidence: 89%
“…This correlated with the formation of eutectic Sn-3.5Ag-0.5Cu (SAC) solder by the addition of Cu in the SA solder (Zhang et al, 2012a;Kotadia et al, 2012). Meanwhile, the overall contact angle for Sn-3.1Ag-0.9Cu (SAC) was within 20 to 30°, and the SAC solder showed better wettability at a reflow temperature of 250°C by producing a larger spreading area and lower contact angle (Ervina and Tan, 2013). Although the wettability of the SAC was Ͻ 50°, and this angle was sufficient to produce better joints (Noor et al, 2010), little research has been done based on the wettability of the SAC solder system.…”
Section: Wettability Properties Of Sacmentioning
confidence: 89%
“…Moreover, Nousia et al [26], after 45-week storage of milk ice cream enriched with Lactobacillus acidophilus LMGP-21381, also did not notice significant differences from the original values. Ervina et al found that the addition of avocado to non-dairy ice cream reduces the acidity of the product, but no statistically significant differences were found compared to the control sample [15]. This is related to the susceptibility of probiotic bacteria to dying under conditions of too low pH.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation-reduction potential is an important indicator for monitoring and estimating oxidative changes in the product. In our study, this parameter is of particular importance due to the used raw material-avocado, which mainly contains monounsaturated fatty acids susceptible to oxidation processes [15]. The fact that no significant changes were observed between the values obtained in the 4th and 8th week of freezing storage may indicate the production of metabolites by the used LAB strain that affect the stability of reducing properties during process [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better wetting occurs when the resultant wetting angle is small. The wetting angle depends on various factors, and these are the PCB finish, the solder alloy, flux, soldering atmosphere, surface roughness, test temperature, solder-substrate interactions and other factors (Ervina et al, 2013). Despite this, accurate determination and repeatability in the measurement of wetting angles has been debated (Sattiraju et al, 2002).…”
Section: Wetting Anglementioning
confidence: 99%